Demonstration of the Google Earth as a Tool in Learning the Earth Physics - Nur Islami (Universitas Riau, 2018)
Earth Physics is a course at the Physics Education Program Study, University of Riau, Indonesia. The problem facing by students were the student commonly not able to imagine the rotation effect and the tilt of rotation axis to some phenomenon. Furthermore the students were difficult to imagine the subduction zone of two tectonic plates. This study was demonstrate some assignments to the student regarding the use Google Earth in the learning the earth physically. In this study, a total of 38 students were chosen to use the Google Earth as an interactive learning media. To demonstrate the Google Earth in the learning process, several assignments have been given to the students. The first was to compare the distance measurement manually and through Google Earth. The second demonstration was to define some selected areas. The third was to demonstrate the tilt axis of rotation effect on the earth. The last was a mini project to demonstrate the use of Google Earth in imagine of the subduction of two tectonic plates. The result shows that mostly students (92%) were able to reconstruction the process involved in the assignment although a few of them cannot explain well. Whilst, 8% of the student were still difficult to reconstruction the process involved in the assignment, although they can submit all the assignments with fairly well. Finally, the Google Earth is generally success used in the demonstration of earth physics subject learning media.